Multidisciplinary Futures of UN Peace Operations
XIX, 279 p. 6 illus., 5 illus. in color.
Keywords: “This collection of essays is a rich survey of the challenges facing the UN and an examination of the opportunities offered by partnerships, technology and reform.” — Roger Mac Ginty, Professor in Defence, Development and Diplomacy, Durham University, UK. “This volume shines because its contributions showcase the complex nature of contemporary peacekeeping and the multiple operational challenges it must evolve to address.” — Dr Katharina P. Coleman, Associate Professor of Political Science, University of British Columbia, Canada. “This book brings together new voices and fresh ideas on future pathways for UN peace operations.” — Dr Jenna Russo, Head of the Brian Urquhart Center for Peace Operations, International Peace Institute, USA Alexander Gilder is Associate Professor of International Law and Security at the School of Law, University of Reading, UK and Associate Faculty at the School of Humanitarian Studies, Royal Roads University, Canada David Curran is Associate Professor and Research Group Leader: Security, Vulnerability and Resilience at the Centre for Trust, Peace, and Social Relations, Coventry University, UK Georgina Holmes is Lecturer in Politics and International Studies at the School of Social Sciences and Global Studies, The Open University, UK. Fiifi Edu-Afful is Senior Research Fellow at the Kofi Annan International Peacekeeping Training Centre, Ghana.